Tantalum-Doped TiO(2) Prepared by Atomic Layer Deposition and Its Application in Perovskite Solar Cells - Hsu, Chia-Hsun (Nanomaterials (Basel), 2021)
Tantalum (Ta)-doped titanium oxide (TiO(2)) thin films are grown by plasma enhanced atomic layer deposition (PEALD), and used as both an electron transport layer and hole blocking compact layer of perovskite solar cells. The metal precursors of tantalum ethoxide and titanium isopropoxide are simultaneously injected into the deposition chamber. The Ta content is controlled by the temperature of the metal precursors. The experimental results show that the Ta incorporation introduces oxygen vacancies defects, accompanied by the reduced crystallinity and optical band gap. The PEALD Ta-doped films show a resistivity three orders of magnitude lower than undoped TiO(2), even at a low Ta content (0.8–0.95 at.%). The ultraviolet photoelectron spectroscopy spectra reveal that Ta incorporation leads to a down shift of valance band and conduction positions, and this is helpful for the applications involving band alignment engineering. Finally, the perovskite solar cell with Ta-doped TiO(2) electron transport layer demonstrates significantly improved fill factor and conversion efficiency as compared to that with the undoped TiO(2) layer.